Associations of blood UCH-L1 and NfL levels with cognitive dysfunction in Parkinson's disease patients. (1st May 2023) - Dong, Linrui; Chang, Qingqing; Ma, Jianjun; Liu, Chuanze; Guo, Dashuai; Li, Xiaohuan; Yang, Dawei; Fan, Yongyan; Liang, Keke; Li, Dongsheng; Gu, Qi
Highlights: This study showed that in Chinese PD patients, old age, low education level, female sex, and severe motor symptoms were risk factors for cognitive impairment. Decreased UCH-L1 levels and elevated NfL levels in the blood were related to cognitive decline in PD patients; additionally, this study is the first to report a negative correlation between UCH-L1 and NfL levels. We found that UCH-L1 and NfL levels had high sensitivity and specificity in the diagnosis of cognitive impairment in Parkinson's disease, especially UCHL1 levels. These proteins are promising biomarkers for diagnosing cognitive impairment in Parkinson's disease. Abstract: Objective: Ubiquitin carboxy-terminal hydrolase L1 (UCH-L1) and Neurofilament light chain (NfL) are associated with Lewy body formation, Lewy bodies are the main pathological feature of Parkinson's disease (PD). The relationship between UCH-L1 and PD cognition remains unclear, and NfL is an important marker of cognitive impairment. The aim of this study is to investigate the relationship among serum UCH-L1 levels, plasma NfL levels and cognitive dysfunction in PD patients. Results: There were significant differences in UCH-L1 and NfL levels among PD patients with normal cognitive function (PD-CN), PD patients with mild cognitive impairment (PD-MCI), and PD-dementia patients (PDD) (P < 0.001; P < 0.001). The PDD group had lower levels of UCH-L1 (Z = 6.721, P < 0.001; Z = 7.577, P < 0.001) and higher levels of NfL (Z = −3.626, P = 0.001; Z = −2.616P = 0.027) than the PD-NC and PD-MCI groups. Serum UCH-L1 levels were positively correlated with MMSE scores, MoCA scores, and its subitems in PD patients (P < 0.001), and plasma NfL levels were negatively correlated with MMSE scores, MoCA scores, and its items (P < 0.01) (except for "abstract"). Conclusion: Decreased UCH-L1 levels and elevated NfL levels in the blood are associated with cognitive dysfunction in PD; thus, these proteins are potential biomarkers for the diagnosis of cognitive dysfunction in PD patients.